Common mental disorders and associated factors among Ethiopian prisoners: a systematic review and meta-analysis - Fentahun, Setegn; Takelle, Girmaw Medfu; Rtbey, Gidey; Andualem, Fantahun; Tinsae, Techilo; Tadesse, Gebresilassie; Melkam, Mamaru (Frontiers in Psychiatry, 2023)
Background Common mental disorders are a major public health concern in the world and negatively influence people’s psychological, physical, economic, and overall well-being. Since prisoners live with restricted freedom and lack regular social interaction like communication with family and friends, the prevalence of common mental disorders is frequently found to be higher among prisoners compared to the general population. Therefore, this systematic review and meta-analysis aimed to estimate the pooled prevalence of common mental disorders and their associated factors among prisoners in Ethiopia. Methods The primary published studies were searched by using different databases like PubMed, Google Scholar, CINHAL, and African Journal Online. A total of eight primary articles that assessed the prevalence and associated factors of common mental disorders among Ethiopian prisoners were included in this systematic review and meta-analysis. The data were extracted using the data extraction format in a Microsoft Excel spreadsheet and exported to Stata version 14 for further analysis. The statistical heterogeneity was assessed by the I2 test. Due to the presence of heterogeneity among included studies, a random effect meta-analysis model was employed. Egger’s weighted regression test and funnel plots were used to check the presence of publication bias. Results A total of 8 primary studies with 3,585 study participants were included in this systematic review and meta-analysis. The pooled prevalence of common mental disorders among Ethiopian prisoners was 62.29% with a 95% CI (50.94, 73.65). The subgroup analysis based on regional state revealed that the pooled prevalence of common mental disorders in Amhara, Oromia, and the other two regions (Addis Ababa and SNNPR) was 72.4, 50.23, and 54.25%, respectively. History of mental illness (AOR = 6.21, 95% CI: 3.27, 11.80), poor social support (AOR = 3.90, 95% CI: 1.45, 10.51), and traumatic life events (AOR = 3.63, 95% CI: 1.04, 12.73) were significantly associated with a common mental disorder in this review. Conclusion In this systematic review and meta-analysis, the pooled prevalence of common mental disorders among prisoners was high. Therefore, improving the delivery of mental health services in correctional institutions has a major contribution to the reduction of the disorder, and incarcerated people require more attention and early intervention for common mental disorders.